Accelerating Complete Phytoplasma Genome Assembly by Immunoprecipitation-Based Enrichment and MinION-Based DNA Sequencing for Comparative Analyses - Tan, Choon Meng; Lin, Yu-Chen; Li, Jian-Rong; Chien, Yuan-Yu; Wang, Chien-Jui; Chou, Lin; Wang, Cheng-Wei; Chiu, Yi-Ching; Kuo, Chih-Horng; Yang, Jun-Yi (Frontiers in Microbiology, 2021)
Phytoplasmas are uncultivated plant-pathogenic bacteria with agricultural importance. Those belong to the 16SrII group, represented by ‘Candidatus. P. aurantifolia’, have a wide range of plant hosts and cause significant yield losses in valuable crops such as pear, sweet potato, peanut, and soybean. In this study, a method that combines immunoprecipitation-based enrichment and MinION long-read DNA sequencing was developed to solve the challenge of phytoplasma genome studies. This approach produced long reads with high mapping rates and high genomic coverage that can be combined with Illumina reads to produce complete genome assemblies with high accuracy. We applied this method to strain NCHU2014 and determined its complete genome sequence, which consists of one circular chromosome with 635,584 bp and one plasmid with 4,224 bp. Although ‘Ca. P. aurantifolia’ NCHU2014 has a small chromosome with only 471 protein-coding genes, it contains 33 transporter genes and 27 putative effector genes, which may contribute to obtaining nutrients from hosts and manipulating host developments for their survival and multiplication. Two effectors, the homologs of SAP11 and SAP54/PHYL1 identified in ‘Ca. P. aurantifolia’ NCHU2014, have the biochemical activities in destabilizing host transcription factors, which can explain the disease symptoms observed in infected plants. Taken together, this study provides the first complete genome available for the 16SrII phytoplasmas, as well as contributes to the understanding of phytoplasma pathogenicity.